Distinct physiological responses of tomato and cucumber plants in silicon-mediated alleviation of cadmium stress - Wu, Jiawen; Guo, Jia; Hu, Yanhong; Gong, Haijun (Frontiers in Plant Science, 2015)
The alleviative effects of silicon (Si) on cadmium (Cd) toxicity were investigated in cucumber (Cucumis sativus L.) and tomato (Solanum lycopersicum L.) grown hydroponically. The growth of both plant species was inhibited by 100 μM Cd, but Si application counteracted the adverse effects on growth. Si application significantly decreased the Cd concentrations in shoots of both species and roots of cucumber. The root-to-shoot transport of Cd was depressed by added Si in tomato whereas it was increased by added Si in cucumber. The total content of organic acids decreased in tomato leaves but increased in cucumber roots and leaves under Cd stress. Si application also increased the cell wall polysaccharide levels in the roots of both species under Cd toxicity. Si-mediated changes in levels of organic acids and cell wall polysaccharides might contribute to the differences in Cd transport in the two species. In addition, Si application also mitigated Cd-induced oxidative damage in both species. The results indicate that there were different mechanisms for Si-mediated decrease in shoot Cd accumulation: in tomato, Si supply decreased root-to-shoot Cd transport; whereas in cucumber, Si supply reduced the Cd uptake by roots. It is suggested that Si-mediated Cd tolerance is associated with different physiological responses in tomato and cucumber plants.